Keberadaan Nematoda Aphelenchoides besseyi pada Benih Padi Varietas Lokal di Kabupaten Samosir, Sumatera Utara: The Presence of the Nematode Aphelenchoides besseyi on Seeds of Local Rice Varieties in Samosir Regency, North Sumatra - Sitanggang, Della; Supramana, Supramana; Kurniawati, Fitrianingrum (Jurnal Fitopatologi Indonesia, 2024)
The Presence of the Nematode Aphelenchoides besseyi on Seeds of Local Rice Varieties in Samosir Regency, North Sumatra Aphelenchoides besseyi is one of the important nematode parasites in rice plants. This research aims to determine the presence of A. besseyi in seeds of local rice varieties from three sub-districts in Samosir Regency, namely Pangururan, Sianjur Mula-Mula, and Palipi. Nematodes were extracted from 400 rice seeds of each variety using a modified Baermann funnel method. Rice seeds were cut at the hilum, soaked in water, and incubated in the dark room for 24 hours at 20 °C. Nematodes were identified based on morphological and morphometry characteristics. Morphometry measurements of A. besseyi were carried out on 70 female nematodes and 10 male nematodes. The nematode A. besseyi were found in the ‘Si Serang’, ‘Saratus Ari’, ‘Si Pining’, and ‘Si Bandung’ varieties with populations of 5 to 13 individuals per 10 g or 400 grains of rice seeds. The nematode A. besseyi was successfully identified based on morphological characteristics including a slender body, set-off lips, thin stylet, large median bulbus, and star-shaped mucro at the tip of the tail. Male nematodes have curved tail tips with spicules shaped like rose thorns. The body size of the A. besseyi from the local rice variety Samosir is smaller than similar nematodes size reported previously.